Estudio de prefactibilidad para la instalación de una planta procesadora de hojuelas de quinua - Aliaga Polo, Juan Diego (2019)
The following research project presents a preliminary study for the implementation of a processing plant of quinoa flakes in boxes of 300 grams. Throughout this, various methodological and technical elements have been used that encompass knowledge acquired through the career of Industrial Engineering, which have made possible the design, formulation and evaluation of this investment project. In the first chapter, the general guidelines are presented from which the research work will be guided, seeking to meet the objectives and verify the hypothesis. The second chapter, market study, evaluates and seeks to verify the existence of a demand capable of acquiring the product. With respect to the third chapter, plant location, the optimal location for the project is defined by the factor ranking method. The fourth chapter, plant size, allows defining the maximum and minimum size limits required for the project. The fifth chapter, project engineering, covers the selection of technology and machinery suitable for the production process and the variables involved in it, the description thereof, the capacity and production plan and the requirements related to quality, environment and security. In addition, it presents the determination of various factors that conclude in the plant layout. The sixth chapter exposes the formation of the business organization and the personnel required for the operation of the project. The seventh chapter involves the detail of the required investment, the operational and financial budgets, as well as the economic and financial evaluation of the project. Finally, the eighth chapter presents the impact that the execution of the project will have on society. This is mainly related to the economic contribution and job creation.